Fascicles and the interfascicular matrix show decreased fatigue life with ageing in energy storing tendons. (1st July 2017) - Thorpe, Chavaunne T.; Riley, Graham P.; Birch, Helen L.; Clegg, Peter D.; Screen, Hazel R.C.
Graphical abstract: Abstract: Tendon is composed of rope-like fascicles bound together by interfascicular matrix (IFM). The IFM is critical for the function of energy storing tendons, facilitating sliding between fascicles to allow these tendons to cyclically stretch and recoil. This capacity is required to a lesser degree in positional tendons. We have previously demonstrated that both fascicles and IFM in energy storing tendons have superior fatigue resistance compared with positional tendons, but the effect of ageing on the fatigue properties of these different tendon subunits has not been determined. Energy storing tendons become more injury-prone with ageing, indicating reduced fatigue resistance, hence we tested the hypothesis that the decline in fatigue life with ageing in energy storing tendons would be more pronounced in the IFM than in fascicles. We further hypothesised that tendon subunit fatigue resistance would not alter with ageing in positional tendons. Fascicles and IFM from young and old energy storing and positional tendons were subjected to cyclic fatigue testing until failure, and mechanical properties were calculated. The results show that both IFM and fascicles from the SDFT exhibit a similar magnitude of reduced fatigue life with ageing. By contrast, the fatigue life of positional tendon subunits was unaffected by ageing. The age-related decline in fatigue life of tendon subunits in energy storing tendons is likely to contribute to the increased risk of injury in aged tendons. Full understanding of the mechanisms resulting in this reduced fatigue life will aid in the development of treatments and interventions to prevent age-related tendinopathy. Statement of Significance: Understanding the effect of ageing on tendon-structure function relationships is crucial for the development of effective preventative measures and treatments for age-related tendon injury. In this study, we demonstrate for the first time that the fatigue resistance of the interfascicular matrix decreases with ageing in energy storing tendons. This is likely to contribute to the increased risk of injury in aged tendons. Full understanding of the mechanisms that result in this reduced fatigue resistance will aid in the development of treatments and interventions to prevent age-related tendinopathy.